ASSESSING THE CONTRIBUTION OF DATE PRODUCTION TO IRAQ'S GROSS DOMESTIC PRODUCT FROM 2004 TO 2020 - Mahdi Alwan Rahima Al-Uqabi (Scholar Express Journals, 2022)
The study assessed the influence of dates' productivity and contribution to the GDP, as well as their disadvantage to rising rates of economic expansion. The standard investigation indicated a direct relationship between each of the independent variables (date prices and the average productivity of dates) and the dependent variable, which is consistent with the logic of economic theory (GDP). Because of Iraq's economic comparative advantage, the study drew many conclusions and recommendations for enhancing date exports
Keywords: Income diversify; rentieral countries; tax; reality